Investigating the contribution of the unfolded protein response to prostate cancer bone metastasis - Kaya, Zeynep (Journal of the Nuffield Department of Surgical Sciences, 2021)
Zeynep Kaya, John C. Christianson, Ian G. Mills, Srinivasa R. Rao, Claire M. Edwards The majority of deaths from PCa arise following metastasis, particularly to the skeleton. ER stress and the unfolded protein response (UPR) promote primary PCa, however the contribution of the UPR to PCa bone metastasis remains unknown. The aim of this work was to determine the role of the UPR in PCa bone metastasis, focusing on the osteogenic potential of PCa cells, EMT and migration, and PCa-induced bone disease. Using paired cell lines ARCaPE and ARCaPM which differ in their epithelial (E) and mesenchymal (M) characteristics, we found that components of IRE1 and ATF6 pathways are higher in ARCaPE cells than in ARCaPM and decreased upon osteogenic differentiation of ARCaPM cells. Inhibition of the IRE1 or PERK pathway increased ALP activity in ARCaPM cells. Inhibition of specific arms of the UPR produced a varied response in EMT markers with no effect on migration of ARCaPM cells. Increasing ER stress using tunicamycin significantly reduced migration of ARCaPM cells. The bone disease associated with PCa bone metastases is driven by alterations in a complex signaling network, including the RANKL/OPG pathway and Wnt signaling. ER stress, induced by tunicamycin, decreased RANKL and Dkk1 expression and increased OPG expression in ARCaPM cells. This osteolytic response to ER stress was blocked by PERK inhibition. Taken together, my research demonstrates that the UPR has multiple effects in bone metastatic PCa cells, including a reduction in migration and in osteolytic factors following UPR activation, suggesting a novel mechanism by which the UPR may modulate PCa-induced bone disease.